2011
DOI: 10.17221/1573-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrition affects the composition of follicular fluid and transcript content in gilt oocytes

Abstract: Metabolomics focused on reproduction have been the subject of special interest in the past decade. Metabolite profiling provides detailed information on the status of follicular fluid and follicular cells which accompany the growing oocyte. Although nutrients present in the diet reach oocytes via the follicular fluid, it is not evident whether oocyte/embryo quality can be predicted based on the follicular fluid composition. Since this phenomenon has not yet been investigated in the pig, the aim of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…In contrast the findings of this study and previous research, some researchers highlighted the vital role and beneficial effects of palmitic acid on oocyte maturation [29, 30]. …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast the findings of this study and previous research, some researchers highlighted the vital role and beneficial effects of palmitic acid on oocyte maturation [29, 30]. …”
Section: Discussioncontrasting
confidence: 99%
“…They suggested modifications in the types of consumed fats in these patients [37]. Another study showed an association between trans-unsaturated fat consumption and incidence of endometriosis [29]. Further studies with larger sample size are, hence, required to assess the correlations of serum and follicular fluid levels of FAs with diet and severity of endometriosis among infertile women.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolite profiling studies have been conducted on FF to investigate the effects of diet on oocyte quality. Warzych et al [ 147 ] measured FF levels of fatty acids, using gas chromatography (GC), in pigs fed either a control diet or a diet with elevated fatty acid levels. They found that diet had a significant influence on the fatty acid content of FF and suggested that the alterations in certain fatty acids had a positive impact on oocyte quality [ 147 ].…”
Section: Resultsmentioning
confidence: 99%
“…Warzych et al [ 147 ] measured FF levels of fatty acids, using gas chromatography (GC), in pigs fed either a control diet or a diet with elevated fatty acid levels. They found that diet had a significant influence on the fatty acid content of FF and suggested that the alterations in certain fatty acids had a positive impact on oocyte quality [ 147 ]. Contradicting this, Sinclair et al [ 135 ] found FF fatty acid composition had no predictive value with regard to oocyte quality in cows.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Zeron et al (2002) demonstrating greater numbers of high quality oocytes with improved membrane integrity on chilling when ewes received diets supplemented with fish oil adds credence to this anticipation of specific benefits. So too does the recent observation by Warzych et al (2011) of enhanced expression of a marker gene (EEF1A1) for oocyte competence in the oocytes of pigs given a dietary supplement of docosahexaenoic acid.…”
Section: Introductionmentioning
confidence: 99%